2020
DOI: 10.1590/1808-057x201909620
|View full text |Cite
|
Sign up to set email alerts
|

Identifying outliers in asset pricing data with a new weighted forward search estimator

Abstract: The purpose of this work is to present the Weighted Forward Search (FSW) method for the detection of outliers in asset pricing data. This new estimator, which is based on an algorithm that downweights the most anomalous observations of the dataset, is tested using both simulated and empirical asset pricing data. The impact of outliers on the estimation of asset pricing models is assessed under different scenarios, and the results are evaluated with associated statistical tests based on this new approach. Our p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…It also presents an alternative robust portfolio beta estimation approach for comparing asset pricing models. (Aronne et al, 2020). This study uses ESG data to create an automated trading strategy and assess a company's ESG premium and ESG alpha.…”
Section: Introductionmentioning
confidence: 99%
“…It also presents an alternative robust portfolio beta estimation approach for comparing asset pricing models. (Aronne et al, 2020). This study uses ESG data to create an automated trading strategy and assess a company's ESG premium and ESG alpha.…”
Section: Introductionmentioning
confidence: 99%
“…Although the GARCH model is very general, there are serious challenges, especially when there are outliers. Previous studies have found that outliers can have detrimental effects on parameter estimate [10][11][12] , identification and estimation 13,14 and forecasting 13,15 . Therefore, robust methods are more preferred by researchers to reduce the influence of outliers.…”
Section: Introductionmentioning
confidence: 99%